Epilepsy: Evidence-based management - Hussain, Mohammad Enayet (Bangladesh Journal of Medicine, 2023)
Epilepsy is a chronic neurological disorder characterized by recurrent seizures. It affects millions of people worldwide and can have a significant impact on a person’s quality of life. Evidence-based management is gaining popularity in all fields of Medicine. In the treatment of epilepsy it involves the use of proven strategies and interventions based on the best available research like systematic reviews and meta analysis. The goal of evidence-based management is to achieve seizure control while minimizing adverse effects and improving quality of life. Close collaboration between healthcare professionals, patients and caregivers is essential to developing and implementing effective management plans. Ongoing research and evaluation of management strategies are crucial to continuously improving the quality of care for the people with epilepsy. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 183